2017
DOI: 10.1063/1.4979946
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous beating and synchronization of extensile active filament

Abstract: We simulate a semi-flexible active filament that exhibits spontaneous oscillations on clamping and show self-propulsion when left free. The activity on the filament relies on the nano-dimers distributed at regular intervals along the chain. With an emphasis on the spontaneous beating of a clamped filament, we demonstrate that the two competing forces necessary for oscillation are the elastic forces due to polymer rigidity and the active forces due to chemical activity. In addition, we also study the synchroniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
1
18
1
Order By: Relevance
“…We estimate ω for different strengths of P e as well as for different torsion parameters. We find that ω grows with P e and follows the scaling relation ω ∼ P e 4/3 as reported earlier [25,49]. Interestingly, ω shows a weak dependence on the torsion rigidity parameter ρ = κ t /κ b .…”
Section: A Periodic Motion Of Filamentsupporting
confidence: 87%
“…We estimate ω for different strengths of P e as well as for different torsion parameters. We find that ω grows with P e and follows the scaling relation ω ∼ P e 4/3 as reported earlier [25,49]. Interestingly, ω shows a weak dependence on the torsion rigidity parameter ρ = κ t /κ b .…”
Section: A Periodic Motion Of Filamentsupporting
confidence: 87%
“…The synchronization of beating chains has been found in other systems such as semi-flexible active filaments 34 and tails of swimming sperms 35 . It was suggested that the hydrodynamic interaction plays an important role in the synchronous beating pattern.…”
Section: Discussionmentioning
confidence: 91%
“…While the phenomenology of active particle systems is well explored, active polymers have been considered only more recently. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Here, interest is primarily focused on the dynamics of the collective behavior, 26,27,31,33 but to date still relatively little is known on the kinetics of the collapse transition of a single active polymer and the emerging structures during the associated coarsening process. For passive polymers, on the other hand, along with the equilibrium aspects of this transition, [41][42][43][44] the latter nonequilibrium phenomena [45][46][47][48][49][50][51][52][53][54] have been studied extensively for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas these aspects of the nonequilibrium kinetics are quite well understood for lattice and off-lattice models of passive polymers, 45,[47][48][49][50][51][52][53] for active polymers there have been only recent computational efforts within Langevin or Brownian dynamics frameworks, with added self-propulsion through an extra active force term. [27][28][29][30][31][32]35,36 For instance, Bianco et al 32 have observed in Brownian dynamics simulations an activity induced collapse transition of a single polymer. In experiments also, filaments with active elements are being realized, e.g., by joining chemically synthesized artificial colloidal or Janus particles via DNAs.…”
Section: Introductionmentioning
confidence: 99%